Psychological strengths and emotional difficulties of students with separated parents: A basis for counseling intervention program - Sarmiento, J. M. (International Journal of Agricultural Technology, 2015)
The study was conducted primarily to determine the Psychological Strengths and Emotional Difficulties of freshmen students of Quirino State University, Diffun, Quirino for school year 2014-2015. Frequency counts and percentages on the description of the profile of the student-respondents in terms of gender; age; birth order; number of siblings; parents’ educational attainment; parents’ occupation; and absent parent; means on descriptions of the respondents’ psychological strengths and emotional difficulties. The study conducted is a descriptive type of research which enabled the researcher to determine and describe the Psychological Strengths and Emotional Difficulties of the respondents. The findings are used in the pursuit of implementing a counseling intervention program with emphasis on respondents’ psychological strengths in resolving the emotional difficulties of the respondents. The respondents’ psychological strengths and emotional difficulties were determined using an adopted questionnaires consisting of 35 items for psychological strengths while 20 items for \emotional difficulties. The data were subjected to appropriate statistical tools using computer application. It was found out that (1)The respondents of the study are mostly females with the age of 16, are first born children and from big family with 4 and above number of siblings; (2) The parents’ educational attainment is mostly high school graduate; (3) The occupations of the fathers are mostly self-employed while the mothers are OFW; (4) Most of the respondents are living with their grandparents and relatives since parents’ separation; (5) In general, the respondents’ psychological strengths are revealed in all categories. However, the Cognitive and Appraisal Skills has obtained the highest mean followed by Interpersonal Skills and Supports with which the outlook for strength based counseling intervention is seen better to process; and (6) the most common emotional difficulty among the respondents was revealed along peer problems.